Patient Adherence and Elimination of Helicobacter Pylori Infection with Once-Daily Triple Therapy Versus Traditional Triple Therapy: A longitudinal study - Nadeem, Nazeer Ahmed, Hyder Wajid Abbasi, Khadim Hussain Samejo, Mohsin Ali, Sheikh Muhammad Taqqi Anwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the patient Adherence and Elimination of Helicobacter pylori Infection with Once-Daily Triple Therapy versus Traditional Triple Therapy Study design: A longitudinal study Place and Duration: This study was conducted at Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences Gambat Pakistan from Faburay 2020 to February 2021. Methodology: A total of 159 patients with aggressive peptic ulcer disease were checked positive for rapid urease exam or 13C-UBT had been provided either once-daily (Tinidazole 1000 milligrams + Azithromycin 500 milligrams +Rabeprazole 40 milligrams) or twice-daily (Amoxicillin 1000 milligrams +Clarithromycin 500 milligrams +Esomeprazole 40). The fast urease exams with 13C-UBT were performed ten weeks following the end of the medication. Pill counting, standardized surveys, and interviews were used to assess compliance and side effects. Results: When compared to the twice-daily cohort, patient adherence was shown to be higher in the once-daily cohort (84.8 percent) (68.8 percent) respectively. Meanwhile, 74.6 percent of the participants tested negative for H. pylori following therapy with the once-daily prescription and reported symptomatic improvement. The standard regime, on the other hand, resulted in 68.7% of the individuals testing negative to UBT and symptomatic alleviation (p=0.4063). Conclusion: No statistically substantial variation in elimination frequencies between the two regimes was observed. The once-daily prescription, on the other hand, had improved drug adherence than the standard treatment plan, indicating that it could be a secure and a superior tolerated substitute to traditional triple treatments, particularly for patients who do not adhere to the regimen. To corroborate the findings, more research should be done.